El modelo educativo contable en el servicio nacional de aprendizaje (SENA) (2017)
The author makes an analysis of the educational model developed by the National Apprenticeship Service —SENA— institution with a long tradition in the training of technicians and technologists in various areas of accounting practice. It emphasizes the relationship between the curricular design and the realities of the apprentices of the institution, and how they respond to problems that are not addressed or identified in professional training programs.